2
$\begingroup$

First of all, I'm not a mathematican in any sense, I'm just curiuous sometimes. So please forgive me for not being rigorous in stating my actual problem.

Given a (non-abelian) group with its usual axioms, consisting of the set $G$ (lets call the group also $G$) and an operation $\cdot$, do I have to proof that from $$h\cdot g=e$$ follows that $$(h\cdot g)\cdot g^{-1}=e\cdot g^{-1}$$ , where $h,g \in G$ and $g^{-1}$ is the inverse element of $g$ and $e$ is the neutral element?

In principle this question is very similar to

Algebra: What allows us to do the same thing to both sides of an equation?

but if I got it right, a group doesn't need to be composed of "numbers". It can be anything, such as a rotation maybe or a far more abstract object I can't even imagine

So basically my question is, if the answer to the related question applies to any group in general or if I have to prove this somehow?

Thanks in advance and sorry for my poor english- and math-skills.

$\endgroup$
  • $\begingroup$ Yes, it works also for "non numbers" (as per many similar question linked to the linked question); it is enough that the operation is defined between the objects you are dealing with, and it is always true that : "if $a=b$, then $(a \text { op } c = b \text { op } c)$. See rules for equality. $\endgroup$ – Mauro ALLEGRANZA Oct 21 '19 at 15:12
  • $\begingroup$ Yes! The inverse in a group is unique! Assume $x^{-1}=a^{-1}$. The definition of the inverse gives us $x^{-1} x = e$ and if $x^{-1}=a^{-1}$ that is equivalent to $xa^{-1} =e$ and multiplying with $a$ gives $x=a$. $\endgroup$ – cptflint Oct 21 '19 at 15:19
  • $\begingroup$ Doesn't even need to be a group. Applies to everything. If $a$ and $b$ are two names for the same thing, and "$manipulate()$" is a manipulation that has a consistent result determined by its input then $manipulate(a)=manipulate(b)$... Admittedly abstract mathematics can into great detail as to how we can define,interpret, and prove such simple concepts of say "a thing is itself" but that's fairly advanced and abstract. $\endgroup$ – fleablood Oct 21 '19 at 15:25
  • 1
    $\begingroup$ @cptflint although that is what the op was eventually trying to show, his/her question was much more basic. S/he was asking how we can multiply both sides by $a$ and if that is something that needs to be prove. If $M=N$ then do we know $Ma=Na$. $\endgroup$ – fleablood Oct 21 '19 at 15:28
  • 1
    $\begingroup$ Subtle side issue: To say: if $a=b$ then $manipulate(a)=manipulate(b)$ requires that "$manipulate()$" is well-defined and consistent. I think some confusion comes from things such as. If $a=b$ then $a^2=b^2$ and $a*0 =b^2$ is true. But if $a^2=b^2$ or $a*0=b*0$ then we can't say $a=b$. But this is because $manipulate$ means "square it" or "multiply" by zero, is well defined and consistent. The concept of "find a number that when squared is equal to the input" or "find a number that when multiplied by zero is the input" are NOT well-defined and are inconsistent. $\endgroup$ – fleablood Oct 21 '19 at 15:35
0
$\begingroup$

If we have, say, $$a=b$$ then for any function $f$, any function at all, we have $$f(a)=f(b)$$ For two values that are the same, inputting them into $f$ will give you the same output, because $f$, being a function, evaluates to a unique value on a given input. Multiplying by $g^{-1}$ on the right is a function. Calling this function $m_g$, we have $$m_g(x) = x\cdot g^{-1}$$ For your equation, we are saying that $$h\cdot g = e$$ so $$(h\cdot g)\cdot g^{-1} = m_g(h\cdot g) = m_g(e) = e\cdot g^{-1}$$ Therefore the manipulation is valid.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.